1997
DOI: 10.1126/science.276.5315.1116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pathogenicity of the Rice Blast Fungus by Saccharomyces cerevisiae α-Factor

Abstract: Magnaporthe grisea is a fungal pathogen with two mating types, MAT1-1 and MAT1-2, that forms a specialized cell necessary for pathogenesis, the appressorium. Saccharomyces cerevisiae alpha-factor pheromone blocked appressorium formation in a mating type-specific manner and protected plants from infection by MAT1-2 strains. Experiments with alpha-factor analogs suggest that the observed activity is due to a specific interaction of alpha-factor with an M. grisea receptor. Culture filtrates of a MAT1-1 strain con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 13 publications
(5 reference statements)
0
29
1
Order By: Relevance
“…Furthermore, culture filtrates of a MAT1-1 strain contained an activity that inhibited appressorium formation of mating type MAT1-2 strains. These findings suggest that activation of the pheromone response pathway may interfere with the signals leading to appressorium formation (24). Following this work, Shen et al reported the isolation of pheromone precursor genes in M. grisea.…”
Section: G␣ Protein Magb Required For Morphogenesismentioning
confidence: 90%
“…Furthermore, culture filtrates of a MAT1-1 strain contained an activity that inhibited appressorium formation of mating type MAT1-2 strains. These findings suggest that activation of the pheromone response pathway may interfere with the signals leading to appressorium formation (24). Following this work, Shen et al reported the isolation of pheromone precursor genes in M. grisea.…”
Section: G␣ Protein Magb Required For Morphogenesismentioning
confidence: 90%
“…The mac1-associated phenotypes are rescued by the addition of cAMP. Exogenous cAMP was also able to suppress the inhibitory effect of Saccharomyces cerevisiae α-factor on appressorium formation by M. grisea (Beckerman et al 1997). Saccharomyces cerevisiae α-factor may inhibit appressorium formation by triggering a pheromone response pathway in M. grisea and by preventing cAMP accumulation (Beckerman et al 1997).…”
Section: Magnaporthe Griseamentioning
confidence: 99%
“…However, the peptide sequence is not known [8]. This study describes the e¡ect of K-mating factor on appressorium development in G. cingulata and the identity of a peptide, produced by G. cingulata, that inhibits appressorium development of G. cingulata conidia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the S. cerevisiae K-mating factor can block the development of M. grisea appressorium [6,8] and that this fungus produces a peptide that inhibits appressorium development. However, the peptide sequence is not known [8].…”
Section: Introductionmentioning
confidence: 99%